Possible important roles of galectins in the healing of human fetal membranes - Chen, Jia-Le; Chen, Yu; Xu, De-Xiang; Chen, Dao-Zhen (Frontiers in Endocrinology, 2022)
The amniotic membrane healing is a complex and dynamic process of replacing devitalized and missing cellular structures and tissue layers. Multiple cells and extracellular matrices, and cell differentiation, migration and proliferation may participate in restoring the integrity of damaged tissue, however this process still remains unclear. Therefore, there is a need to identify and integrate new ideas and methods to design a more effective dressing to accelerate amniotic membrane healing. This review explores the function and role of galectins in the inflammatory, epithelial mesenchymal transition, proliferative migration, and remodeling phases of amniotic membrane healing. In conclusion, the preliminary findings are promising. Research on amnion regeneration is expected to provide insight into potential treatment strategies for premature rupture of membranes.